1999
DOI: 10.1161/01.hyp.34.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclooxygenase-2 Inhibition on Renal Function After Renal Ablation

Abstract: Abstract-Kidney failure is the common end of hypertension and renal diseases. Several authors have suggested that vasodilatory prostaglandins participate in the hemodynamic mechanism responsible for the development of kidney failure. However, the mechanism by which prostaglandins are increased in renal disease is not clear. Recently, 2 isoforms of the enzyme responsible for prostaglandin synthesis, cyclooxygenase, have been described as cyclooxygenase-1 (COX-1), a constitutive isoform, and cyclooxygenase-2 (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
42
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 36 publications
10
42
1
Order By: Relevance
“…As we previously showed [17], 14 days after 5/6 nephrectomy urinary protein excretion was increased from 32.2 ± 5.8 to 102.84 ± 37.32 mg/24h (p = 0.001), this effect persisted for the following 6 weeks (Figure 1(a)). Also SBP was increased from 112.6 ± 12.5 mmHg to 191.8 ± 12.7 mmHg compared with SO rats, 60 days after 5/6 nephrectomy (p < 0.001).…”
Section: Ras Blockade Effect On Renal Functional Parameterssupporting
confidence: 73%
“…As we previously showed [17], 14 days after 5/6 nephrectomy urinary protein excretion was increased from 32.2 ± 5.8 to 102.84 ± 37.32 mg/24h (p = 0.001), this effect persisted for the following 6 weeks (Figure 1(a)). Also SBP was increased from 112.6 ± 12.5 mmHg to 191.8 ± 12.7 mmHg compared with SO rats, 60 days after 5/6 nephrectomy (p < 0.001).…”
Section: Ras Blockade Effect On Renal Functional Parameterssupporting
confidence: 73%
“…Previous studies reported that chronic administration of a selective COX2 inhibitor significantly decreased proteinuria and attenuated development of glomerular sclerosis in rats with reduced renal mass. [43][44][45] However, in our study, celecoxib, administered 1 month after Nx, did not significantly improve renal function in the uremic rats with SHPT. Delayed celecoxib treatment after Nx may contribute to the less-protective effect on renal function.…”
Section: Basic Research Wwwjasnorgcontrasting
confidence: 73%
“…Selective increases in renal cortical COX-2 expression can be detected in the region of the MD in rat remnant kidneys without significant alterations in COX-1 expression (105)(106)(107) and from kidneys with streptozotocin-induced diabetes (108,109). Isolated glomeruli from remnant kidneys also demonstrated selective increases in COX-2 immunoreactivity and increased PGE 2 production, which was inhibited by a COX-2 selective inhibitor (105).…”
Section: Effects Of Cox-2 Inhibitors In Proteinuric Statesmentioning
confidence: 99%
“…Chronic administration of a selective COX-2 inhibitor significantly decreased proteinuria and inhibited development of glomerular sclerosis in rats with reduced functioning renal mass (105,106,119). These effects were seen in the absence of any detectable changes in systemic BP, suggesting that any "renoprotective" effects that were seen with the COX-2 inhibitor were not secondary to modulation of systemic BP (105,120).…”
Section: Effects Of Cox-2 Inhibitors In Proteinuric Statesmentioning
confidence: 99%